Explicit vocabulary instruction: Effects of vocabulary learning on Form Two ESL learners - Mohd Haniff Mohd Tahir; Dianna Suzieanna Mohamad Shah; Mohamad Syafiq Ya Shak; Intan Safinas Mohd Ariff Albakri; Airil Haimi Mohd Adnan (Universitas Syiah Kuala, 2021)
Per its English curriculum, vocabulary instruction is only integrated indirectly in the teaching of reading, writing, listening, and speaking skills in Malaysian schools. ESL learners then may overlook the variety of meanings that a word and its spelling can offer. This research aims to describe the effects of the explicit approach of vocabulary instruction on 30 Form Two (eighth grade) students from a suburban school in Ipoh, Perak, Malaysia. A descriptive style was adopted, and specific vocabulary lessons were used to help students learn the target words. Using descriptive statistics, vocabulary pre- and post-test scores were analysed and compared to determine the impact of this approach. The frequency counts, percentages, mean scores, and standard deviation of the students’ evaluation form responses were analysed. Content analysis was used to transcribe, classify, and categorise qualitative data from the interview session. According to the data, the students’ vocabulary scores increased dramatically in the post-test, with a mean gap of 21.9. The students were also enthusiastic about the teacher’s instructions (M=4.48, SD=0.64) and vocabulary lessons (M=4.34, SD=0.59). It is suggested that the explicit approach of vocabulary instruction, which engages students in exciting vocabulary learning techniques as employed by this study could enhance their vocabulary knowledge.